Integration of Maqashid Sharia in the Operations of Chemical Manufacturing Companies in Indonesia - Lisma Humaidah; A’rasy Fahrullah; Khusnul Fikriyah (UIN Siber Syekh Nurjati Cirebon, 2025)
Manufacturing activities increasingly face demands for ethical governance, worker protection, and environmental responsibility, yet maqāṣid al-sharīʿah is still more frequently operationalized in Islamic finance than in the real sector. This study examines chemical manufacturing operations at PT JM Mutu Utama through a maqāṣid al-sharīʿah review to clarify how operational policies align with maqāṣid objectives and what welfare-related performance implications emerge. A qualitative descriptive–analytical design was employed using semi-structured interviews with five purposively selected informants (QHSE Manager, HR Manager, and three operational staff), field observations, and document analysis (ISO-related certificates, SOPs, and internal reports). Data credibility was strengthened through source and technique triangulation, and analysis followed the Miles–Huberman interactive model. Findings indicate alignment across six maqāṣid dimensions (ḥifẓ al-dīn, al-nafs, al-ʿaql, al-nasl, al-māl, and al-bi’ah), reflected in OHS governance, structured welfare and compensation schemes, competency development, family-supportive policies, and environmental management practices. Welfare-related performance implications appear through enhanced economic security, improved workplace safety and comfort, and strengthened psychosocial well-being. Distributional gaps remain, particularly the limited institutionalization of religious programs for warehouse employees, indicating inclusivity challenges. The study proposes an operational linkage framework connecting manufacturing instruments to maqāṣid objectives to support employee welfare and corporate sustainability in the chemical manufacturing context.Keywords: chemical manufacturing; corporate sustainability; employee welfare; maqāṣid al-sharīʿah; occupational health and safety